Supported zinc dimolybdate hydroxide / silica composites and their use in polymer formulations - Patents.com

JP2024520365A5Pending Publication Date: 2025-04-22J M HUBER CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023571990
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-05-25
Filing Date
2022-05-20
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

Existing polymeric compositions lack effective flame retardancy and abrasion resistance, particularly in applications like printed circuit boards and epoxy molding compounds, where conventional flame retardants pose environmental concerns and drilling processes are inefficient.

Method used

The development of supported zinc dimolybdate hydroxide/silica composites, formed by reacting zinc compounds and molybdenum trioxide with silica in an aqueous system, which are then incorporated into polymer formulations to enhance flame retardancy and reduce abrasion.

Benefits of technology

The composites provide halogen-free flame retardancy, improve drilling processes, and offer thermal stability, reducing the environmental impact while enhancing the performance of polymers in applications such as printed circuit boards and epoxy molding compounds.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000023_0000
    Figure 00000023_0000
  • Figure 00000023_0001
    Figure 00000023_0001
  • Figure 00000023_0002
    Figure 00000023_0002
Patent Text Reader

Abstract

A method for making supported zinc dimolybdate hydroxide / silica composites includes reacting a zinc compound (such as zinc oxide) with molybdenum trioxide in an aqueous system to form a reaction mixture and contacting the reaction mixture with silica to form a supported zinc dimolybdate hydroxide / silica composite. The resulting zinc dimolybdate hydroxide / silica composite contains silica and an amount of zinc dimolybdate hydroxide ranging from 3 to 20 wt%, with generally at least 80 wt% of the zinc dimolybdate hydroxide being present in the form Zn3Mo2O8(OH)2. These supported zinc dimolybdate hydroxide / silica composites are useful in polymer compositions such as PVC-based and epoxy-based formulations.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] (CROSS REFERENCE TO RELATED APPLICATIONS) This application claims the benefit of and priority to U.S. Provisional Patent Application No. 63 / 192,634, filed May 25, 2021, the disclosure of which is incorporated herein by reference in its entirety.

[0002] (Technical field) The present invention relates generally to zinc dimolybdate hydroxide materials, and more specifically to supported zinc dimolybdate hydroxide / silica composites that can be used in polymer compositions to improve flame retardancy and reduce abrasiveness. Summary of the Invention

[0003] This Summary is provided to introduce a selection of concepts in a simplified form that are further described below in the Detailed Description. This Summary is not intended to identify required or essential features of the claimed subject matter, nor is it intended to be used to limit the scope of the claimed subject matter.

[0004] Methods for producing supported zinc dimolybdate hydroxide / silica composites are disclosed and described herein. One such process may include (i) reacting a zinc compound (an illustrative example is zinc oxide) with molybdenum trioxide (MoO3) in an aqueous system to form a reaction mixture, and (ii) contacting (or slurrying) the reaction mixture with silica to form a supported zinc dimolybdate hydroxide / silica composite. Another process for producing supported zinc dimolybdate hydroxide / silica composites may include contacting (or slurrying) zinc dimolybdate hydroxide with silica in an aqueous system to form a supported zinc dimolybdate hydroxide / silica composite.

[0005] Supported zinc dimolybdate hydroxide / silica composites are also disclosed and described herein, which may include (a) silica and (b) zinc dimolybdate hydroxide containing an amount of zinc ranging from 3 to 20 wt %, based on the total weight of the supported zinc dimolybdate hydroxide / silica composite. Typically, at least 80 wt %, often 90 to 100 wt %, of the zinc dimolybdate hydroxide is present in the crystalline form Zn3Mo2O8(OH)2.

[0006] Polymer compositions are also provided herein, and such compositions may include a polymer and any of the supported zinc hydroxide dimolybdate / silica composites disclosed herein (e.g., produced by any of the processes disclosed herein). The relative amounts of polymer and supported zinc hydroxide dimolybdate / silica composite in the composition are not particularly limited, nor is the type of polymer, although the supported zinc hydroxide dimolybdate / silica composite is particularly well suited for use in PVC and epoxy-based formulations.

[0007] Both the foregoing summary and the following detailed description provide examples and are for illustrative purposes only. Thus, the foregoing summary and the following detailed description should not be considered limiting. Furthermore, features or variations may be provided in addition to those described herein. For example, certain aspects may be directed to combinations and subcombinations of various features described in the detailed description. [Brief description of the drawings]

[0008] [Figure 1] 1 is a scanning electron microscope photograph of the spherical fused silica component used in Example 1. [Diagram 2] 1 is a scanning electron micrograph of the supported zinc dimolybdate hydroxide / silica composite of Example 1. [Diagram 3] 1 is a scanning electron micrograph of the supported zinc dimolybdate hydroxide / silica composite of Comparative Example A. [Figure 4]1 shows plots of heat release rate (HRR) curves for the flame retardant polymer compositions of Examples 12-15. [Diagram 5] Photographs of drill bits before and after drilling epoxy plaques of Examples 16-17. [Figure 6] Photographs of drill bits before and after drilling epoxy plaques of Examples 18-19. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] (definition) In order to more clearly define the terms used herein, the following definitions are provided. Unless otherwise stated, the definitions below apply to this disclosure. If a term is used in this disclosure but not specifically defined herein, the definition in the IUPAC Compendium of Chemical Terminology, Second Edition (1997) may be applied unless the definition is inconsistent with other disclosures or definitions to which it applies or unless it renders uncertain or invalid the claims to which it applies. In the event that any definition or usage provided by a document incorporated herein by reference conflicts with the definition or usage provided herein, the definition or usage provided herein shall take precedence.

[0010] In this specification, the subject features are described so that in certain embodiments, different combinations of features can be envisioned.For any embodiment and any feature disclosed herein, all combinations that do not adversely affect the design, composition, process, or method described herein are contemplated and can be exchanged with or without the explicit description of a specific combination.Therefore, unless expressly stated otherwise, any embodiment or feature disclosed herein can be combined to describe the design, composition, process, or method of the invention consistent with this disclosure.

[0011] Although compositions and methods are described herein in terms of "comprising" various components or steps, unless otherwise specified, the compositions and methods may also "consist essentially of" or "consist of" various components or steps.

[0012] The terms "a," "an," and "the" are intended to include plural alternatives, e.g., at least one, unless otherwise specified.

[0013] Generally, groups of elements are designated using the numbering scheme set forth in the version of the Periodic Table of the Elements published in Chemical and Engineering News, 63(5), 27, 1985. In some cases, groups of elements are designated by the common name assigned to the group, e.g., alkali metals for Group 1 elements, alkaline earth metals for Group 2 elements, etc.

[0014] The term "contacting" is used herein to refer to materials or ingredients that may be contacted or combined by blending, mixing, slurrying, dissolving, reacting, processing, compounding, or in any other manner or any suitable method. Unless otherwise specified, the materials or ingredients may be contacted together in any order, in any manner, and for any length of time.

[0015] Molybdenum trioxide (MoO3) may often be referred to as molybdenum trioxide, molybdenum(VI) oxide, molybdenum anhydride (or molybdic acid anhydride). As one skilled in the art would readily recognize, in an (acidic) aqueous environment, molybdenum trioxide may form molybdic acid, as well as other species such as hydrates and molybdates. Thus, when the use of molybdenum trioxide in an aqueous mixture or system is disclosed herein, this is meant to encompass any form of molybdenum species or complexes present in an aqueous environment, such as molybdic acid, hydrates, molybdates, etc., and combinations thereof.

[0016] Although any methods and materials similar or equivalent to those described herein can be used in the practice or testing of the present invention, typical methods and materials are described herein.

[0017] All publications and patents mentioned herein are incorporated by reference herein, e.g., for the purpose of describing and disclosing structures and methodologies described in the publications that might be used in connection with the presently described invention.

[0018] In the present invention, several types of ranges are disclosed. When any type of range is disclosed or claimed, the intent is to individually disclose or claim each possible value that the range may reasonably encompass, including the endpoints of the range, as well as any subranges and combinations of subranges contained therein. As a representative example, the d50 particle size of silica may be within a particular range in various embodiments of the present invention. By disclosing that the d50 particle size may be in the range of 0.2-5 μm, the intent is to indicate that the d50 may be any particle size within that range, for example, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, or 5 μm. Furthermore, the d50 particle size may be any range or combination of ranges, such as 0.2-5 μm, for example, 0.2-2.5 μm, 0.2-1 μm, or 0.25-0.8 μm. Similarly, all other ranges disclosed herein should be interpreted in a similar manner to this example.

[0019] In general, amounts, sizes, formulations, parameters, ranges, or other quantities or characteristics are "about" or "approximately" whether or not expressly stated. The claims include equivalents to the quantities or characteristics whether or not modified by the term "about" or "approximately."

[0020] Detailed Description of the Invention Disclosed herein are supported zinc hydroxide dimolybdate / silica composites containing primarily the crystalline form Zn3Mo2O8(OH)2, methods for making the supported zinc hydroxide dimolybdate / silica composites, and polymer compositions and articles of manufacture containing the supported zinc hydroxide dimolybdate / silica composites.

[0021] (Process for manufacturing the supported composite) Various processes for producing supported zinc dimolybdate hydroxide / silica composite are provided herein. The first process can include (or can consist essentially of, or can consist of) (i) reacting a zinc compound with molybdenum trioxide (MoO3) in an aqueous system to form a reaction mixture, and (ii) contacting (or slurrying) the reaction mixture with silica to form a supported zinc dimolybdate hydroxide / silica composite. The second process for producing supported zinc dimolybdate hydroxide / silica composite can include (or can consist essentially of, or can consist of) contacting (or slurrying) zinc dimolybdate hydroxide with silica in an aqueous system to form a supported zinc dimolybdate hydroxide / silica composite.

[0022] Generally, any of the features of the processes disclosed herein (e.g., the zinc compound, molybdenum trioxide (MoO3), zinc dimolybdate hydroxide, silica, aqueous system, and temperature and pressure conditions under which any steps are performed, etc.) are described herein independently, and these features may be combined in any combination to further describe the disclosed processes. Additionally, unless otherwise noted, other process steps may be performed before, during, and / or after any of the steps recited in the disclosed processes. Additionally, any supported zinc dimolybdate hydroxide / silica composite produced according to any of the disclosed processes is within the scope of the present disclosure and is encompassed herein.

[0023] Referring now to the first process, steps (i) and (ii) may be independently carried out at temperatures typically within the range of 20°C to 95°C, such as, but not limited to, 50°C to 95°C, 70°C to 95°C, 75°C to 90°C, or 80°C to 90°C. In these and other embodiments, these temperature ranges are also meant to encompass situations where step (i) and / or step (ii) are carried out at a series of different temperatures rather than a single fixed temperature within the respective ranges. The pressure at which steps (i) and (ii) are carried out may be, but is not limited to, independently high pressure (e.g., 5 psig to 100 psig), atmospheric pressure, or any suitable subatmospheric pressure. In some cases, steps (i) and (ii) are carried out at atmospheric pressure, eliminating the need for and the associated costs and complexities of a pressurized vessel. Independently, steps (i) and (ii) may be carried out over a wide range of times, such as, but not limited to, 15 minutes to 24 hours, 30 minutes to 12 hours, or 90 minutes to 6 hours. Other suitable temperature, pressure, and time ranges will be readily apparent from this disclosure.

[0024] In step (i), a zinc compound is reacted with molybdenum trioxide in an aqueous system to form a reaction mixture. Any suitable zinc compound may be used, such as zinc oxide, zinc chloride, zinc nitrate, etc. Zinc oxide is often used because it does not introduce other elements (such as halogens or nitrogen) into the process that may need to be removed later. The zinc compound and molybdenum trioxide may be contacted or reacted at a Zn:Mo molar ratio that typically falls within the range of 1:1 to 2:1, based on the total amount of each reactant, regardless of the order of addition, contacting of the reactants, or addition method used. For example, molybdenum trioxide (e.g., a slurry in water) may be added slowly to zinc oxide (e.g., an aqueous solution) at any suitable addition rate and for any suitable time. As one of ordinary skill in the art would readily appreciate, the Zn:Mo molar ratio may change as the reaction proceeds. Thus, the disclosed molar ratio ranges encompass any molar ratio encountered during the reaction in step (i) and during the formation of the reaction mixture. In further aspects of the invention, the Zn:Mo ratio may be from 1.2:1 to 1.8:1, from 1.3:1 to 1.7:1, or from 1.4:1 to 1.6:1. For example, the Zn:Mo molar ratio may be a stoichiometric ratio of 1.5:1 (+ / -10%), reflecting the resultant zinc dimolybdate hydroxide having the formula Zn3Mo2O8(OH)2.

[0025] In step (ii) of the first process, the reaction mixture (aqueous system) is contacted (or slurried) with silica to form a supported zinc dimolybdate hydroxide / silica complex, while in the second process, the zinc dimolybdate hydroxide is contacted (or slurried) with silica in the aqueous system to form a supported zinc dimolybdate hydroxide / silica complex. In both processes, the aqueous system may comprise water (or may consist essentially of water, or may consist of water). The pH of the aqueous system is not particularly limited, and as will be readily recognized by those skilled in the art, the pH of the aqueous system and the pH at which the supported zinc dimolybdate hydroxide / silica complex is formed may vary as the reaction proceeds. If desired, the aqueous system may contain an acid or base to modify or control the pH to a particular range during the first and / or second process.

[0026] Referring now to the second process, the supported zinc hydroxide dimolybdate / silica composite can be formed at a temperature typically within the range of 15°C to 95°C, such as, but not limited to, 15°C to 50°C, or 20°C to 35°C. In these and other embodiments, these temperature ranges are also meant to encompass the situation where the supported zinc hydroxide dimolybdate / silica composite is formed at a series of different temperatures within the respective ranges, instead of a single fixed temperature. The pressure at which the supported zinc hydroxide dimolybdate / silica composite is formed can be, but is not limited to, high pressure (e.g., 5 psig to 100 psig), atmospheric pressure, or any suitable subatmospheric pressure. In some cases, the supported zinc hydroxide dimolybdate / silica composite is formed at atmospheric pressure, thus eliminating the need for a pressurized vessel and the associated costs and complexities. Generally, the supported zinc dimolybdate hydroxide / silica composite may be formed over a wide range of times, such as, but not limited to, 15 minutes to 24 hours, 30 minutes to 12 hours, or 2 hours to 6 hours. Other suitable temperature, pressure, and time ranges will be readily apparent from the present disclosure.

[0027] Optionally, the first and second processes for producing a supported zinc hydroxide dimolybdate / silica composite may further include removing the supported zinc hydroxide dimolybdate / silica composite from the water using any suitable separation technique, such as filtration or centrifugation, as well as combinations of these techniques.

[0028] Optionally, the first and second processes for producing a supported zinc dimolybdate hydroxide / silica composite may further include drying the supported zinc dimolybdate hydroxide / silica composite using any suitable drying conditions. For example, a drying temperature in the range of 50° C. to 200° C., or 100° C. to 150° C. may be used, and drying may be performed at atmospheric pressure or any suitable subatmospheric pressure, for example, less than 150 Torr, or less than 50 Torr.

[0029] If desired, the first and second processes for producing the supported zinc hydroxide dimolybdate / silica composite may further include a step of deagglomerating the supported zinc hydroxide dimolybdate / silica composite, may further include a step of grinding the supported zinc hydroxide dimolybdate / silica composite, or may utilize both deagglomerating and grinding steps.

[0030] (Supported Zinc Dimolybdate Hydroxide / Silica Composite) Consistent with aspects of the present invention, the supported zinc dimolybdate hydroxide / silica composite described herein (or the supported zinc dimolybdate hydroxide / silica composite produced according to any of the processes disclosed herein) may be used in a variety of polymer formulations with beneficial performance properties. In one aspect, the supported zinc dimolybdate hydroxide / silica composite may include (a) silica and (b) zinc dimolybdate hydroxide containing an amount of zinc ranging from 3 to 20 wt % based on the total weight of the supported zinc dimolybdate hydroxide / silica composite. At least 80 wt % of the zinc dimolybdate hydroxide may be present as Zn3Mo2O8(OH)2 in crystalline form.

[0031] The silica component of the supported zinc dimolybdate hydroxide / silica composite (or the silica used in the process for making the supported zinc dimolybdate hydroxide / silica composite) may often have a median particle size (d50) in the range of 0.2-5 μm, 0.2-25 μm, 0.2-1 μm, or 0.25-0.8 μm. Additionally or alternatively, the d100 particle size of the silica may be in the range of 0.6-10 μm, 0.6-5 μm, 0.6-4 μm, 0.7-4 μm, or 0.7-3.5 μm. Additionally or alternatively, the d10 particle size of the silica may be in the range of 0.08-1 μm, 0.08-0.5 μm, 0.1-0.5 μm, or 0.1-0.4 μm. Additionally or alternatively, the silica may have a median particle size (d50) in the range of 2-20 μm. 2 / g, 4~15m 2 / g, 4~12m 2 / g, 5-15m 2 / g, or 5 to 13 m 2 / g Other suitable particle sizes and surface areas will be readily apparent from this disclosure.

[0032] Without being limited thereto, in some embodiments of the present invention, the silica may be fused silica, as opposed to fumed and precipitated silica. Generally, the silica is also spherical silica. Thus, in certain embodiments, the silica component of the supported zinc dimolybdate hydroxide / silica composite (or the silica used in the method of making the supported zinc dimolybdate hydroxide / silica composite) is spherical fused silica. Silica is considered spherical when the average aspect ratio is in the range of 1:1 to 1.4:1, and more often the average aspect ratio is 1:1 to 1.25:1, or 1:1 to 1.1:1. Aspect ratio is defined herein as the longest (measurable) particle dimension divided by the shortest dimension as viewed in a two-dimensional SEM image (e.g., FIG. 1). The average aspect ratio is the average of the aspect ratios of 10 (measurable) particles from the SEM image.

[0033] The supported zinc dimolybdate hydroxide / silica composite described herein (or supported zinc dimolybdate hydroxide / silica composite produced by any process described herein) may contain zinc dimolybdate hydroxide with an amount of zinc ranging from 3 to 20 wt% based on the total weight of the supported zinc dimolybdate hydroxide / silica composite. In another embodiment, the supported zinc dimolybdate hydroxide / silica composite may contain 3 to 18 wt% zinc, in another embodiment, 4 to 16 wt% zinc, and in yet another embodiment, 5 to 15 wt% zinc. Additionally or alternatively, the supported zinc dimolybdate hydroxide / silica may contain 3 to 20 wt% molybdenum, such as, for example, 3 to 18 wt% molybdenum, 4 to 16 wt% molybdenum, or 5 to 15 wt% molybdenum.

[0034] Without being limited thereto, the supported zinc dimolybdate hydroxide / silica composite described herein (or the supported zinc dimolybdate hydroxide / silica composite produced by any process described herein) can often have a median particle size (d50) in the range of 0.3-6 μm, 0.3-2 μm, 0.4-1.8 μm, or 0.5-1.7 μm. Additionally or alternatively, the d100 particle size of the supported zinc dimolybdate hydroxide / silica composite can be in the range of 1-12 μm, 1-8 μm, 1.5-7 μm, 2-7 μm, or 2.5-6 μm. Additionally or alternatively, the d10 particle size of the supported zinc dimolybdate hydroxide / silica composite can be in the range of 0.1-1.5 μm, 0.1-0.8 μm, 0.1-0.7 μm, or 0.2-0.6 μm. Additionally or alternatively, the span ((d90-d10) / d50) of the supported zinc dimolybdate hydroxide / silica composite can be in the range of 1.5 to 5, 1.5 to 4.5, or 2 to 4. Additionally or alternatively, the supported zinc dimolybdate hydroxide / silica composite can have a span of 3 to 20 m. 2 / g, 3-15m 2 / g, 3-12m 2 / g, 4~13m 2 / g, or 4 to 10m 2 / g range of BET surface area. Other suitable particle sizes and surface areas of the supported zinc dimolybdate hydroxide / silica composite will be readily apparent from this disclosure.

[0035] Like silica, the supported zinc hydroxide dimolybdate / silica composites described herein (or supported zinc hydroxide dimolybdate / silica composites produced by any of the processes described herein) can be spherical (average aspect ratio ranging from 1:1 to 1.4:1, more often the average aspect ratio is 1:1 to 1.25:1, or 1:1 to 1.1:1).

[0036] Here, at least 80 wt% of the zinc dimolybdate hydroxide may be present as the crystalline form Zn3Mo2O8(OH)2. For example, at least 80 wt%, at least 85 wt%, at least 90 wt%, or at least 95 wt% may be present as Zn3Mo2O8(OH)2. Thus, substantially all (98-99.5 wt%) or all (100 wt%) of the zinc dimolybdate hydroxide may be present as the crystalline form Zn3Mo2O8(OH)2. Other forms of zinc / molybdenum compounds include ZnMoO4·0.8H2O and ZnMoO4 (zinc molybdate).

[0037] (Polymer Composition) The present invention is also directed to and encompasses any compositions, formulations, composites, and articles of manufacture containing any of the supported zinc hydroxide dimolybdate / silica complexes disclosed herein (and their respective properties or characteristics, such as surface area, particle size, amount of zinc, amount of molybdenum, crystal form, etc.). In certain aspects of the present invention, polymer compositions are disclosed, which may include any suitable polymer(s) and any of the supported zinc hydroxide dimolybdate / silica complexes disclosed herein (or supported zinc hydroxide dimolybdate / silica complexes produced by any of the processes described herein).

[0038] In one embodiment, the polymer in the polymer composition may comprise a thermoplastic polymer, and in another embodiment, the polymer may comprise a thermosetting polymer. In another embodiment, the polymer may comprise polyvinylidene chloride (PVDC), polyvinyl chloride (PVC), chlorinated polyvinyl chloride (CPVC), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), and / or ethylene chlorotrifluoroethylene (ECTFE), either alone or in any combination. In yet another embodiment, the polymer may comprise plasticized PVC or unplasticized PVC. In yet another embodiment, the polymer may comprise rigid PVC, or the polymer may comprise flexible PVC. Generally, rigid PVC may be referred to as unplasticized PVC, and flexible PVC may be referred to as plasticized PVC.

[0039] As one of ordinary skill in the art would readily recognize, PVDC can be referred to as polyvinylidene chloride and also as poly(vinylidene chloride). Similarly, PVC can be referred to as polyvinyl chloride and also as poly(vinyl chloride).

[0040] In one embodiment, the polymer may include an epoxy resin. For example, the polymer may include, either alone or in any combination, bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, phenol novolac epoxy resin, cresol novolac epoxy resin, bisphenol A novolac epoxy resin, bisphenol F novolac epoxy resin, diphenylethylene epoxy resin, epoxy resin having a triazine skeleton, epoxy resin having a fluorene skeleton, triphenylmethane epoxy resin, biphenyl epoxy resin, xylylene epoxy resin, biphenyl aralkyl epoxy resin, naphthalene-based epoxy resin, dicyclopentadiene-based epoxy resin, and / or alicyclic epoxy resin, etc.

[0041] Without being limited thereto, the amount of supported zinc dimolybdate hydroxide / silica complex in the polymer composition can often be in the range of 1-50 phr (parts by weight per 100 parts of resin). Thus, exemplary and non-limiting amounts of supported zinc dimolybdate hydroxide / silica complex in the polymer composition include ranges of 5-50 phr, 2-40 phr, 5-40 phr, 10-50 phr, 10-40 phr, 10-30 phr, or 15-40 phr. Other suitable ranges of the amount of supported zinc dimolybdate hydroxide / silica complex in the polymer composition will be readily apparent from the present disclosure.

[0042] Optionally, the polymer composition may further comprise any suitable additives, non-limiting examples of which include stabilizers, lubricants, inorganic flame retardants (e.g., aluminum trihydrate or magnesium hydroxide), fillers, colorants, curing agents, catalysts or accelerators, or fibers (e.g., glass fibers, carbon fibers, paper fibers, nonwoven fibers), and the like, as well as combinations thereof.

[0043] The article may be formed from and / or include any of the polymer compositions described herein. In one embodiment, the article may include a wire or cable, and in another embodiment, the article may include a printed circuit board. Other suitable articles and end uses will be readily apparent from this disclosure.

[0044] For example, the spherical zinc dimolybdate hydroxide / silica composite can be utilized in at least three applications of industrial composite prepregs, as well as in microelectronics manufacturing, to benefit from improved end product properties and improved manufacturing processes: the first is printed circuit boards (PCBs), the second is epoxy molding compounds (EMCs) such as microchip packaging, and the third is industrial composite prepregs such as aerospace and automotive end uses where flame retardancy and drilling are required.

[0045] Printed circuit boards (PCBs) are prevalent in electronics for consumer and industrial products such as televisions, cell phones, and computers. Manufacturers typically use flame-retardant chemicals to produce circuit boards to ensure fire safety. Flame retardants may completely prevent the start of a fire or may delay the onset of a flashover, slowing the spread stage of a fire and thereby extending the evacuation time frame. In either case, flame retardants serve the primary purpose of reducing the risk of fatalities from fire. However, some flame retardant chemicals have raised concerns about their fate and toxicity if released into the environment. This is the case with Tetrabromobisphenol A or TBBPA. TBBPA is the most widely used flame retardant for PCBs. Here, a single composition offers several benefits such as halogen-free flame retardancy, improved drilling, thermal expansion control, and dimensional stability.

[0046] A basic PCB consists of a flat sheet of insulating material and a layer of copper foil laminated to a substrate. Chemical etching breaks up the copper into features such as individual conductive lines called tracks or circuit traces, pads for connections, vias for passing connections between layers of copper, and solid conductive areas for electromagnetic shielding or other purposes. Printed circuit boards can have multiple copper layers. Two-layer boards have copper on both sides, and multi-layer boards sandwich additional copper layers between layers of insulating material. Conductors on different layers are connected with vias, which are copper-plated holes that act as electrical tunnels through the insulating substrate. Leads on through-hole components often also effectively function as vias. "Through-hole" components are attached by leads that pass through the substrate and are soldered to traces on the other side. Through-hole manufacturing increases the cost of the substrate because many holes must be precisely drilled. PCB holes larger than 76.2 micrometers in diameter are typically drilled using solid-coated tungsten carbide drill bits. Beneficially, the disclosed compositions have high thermal stability and are suitable for lead-free soldering.

[0047] Important properties are the laminate's level of flame retardancy, dielectric constant (er), loss factor (tδ), tensile strength, shear strength, glass transition temperature (Tg), and Z-axis expansion coefficient (how much thickness changes with temperature). Thermal expansion is an important consideration, especially in ball grid array (BGA) and naked die technologies, where glass fibers generally offer the best dimensional stability. As substrate dimensions shrink and frequencies increase, small inhomogeneities such as uneven distribution of glass fibers or other fillers, thickness variations, and air bubbles within the resin matrix and their associated local variations in dielectric constant become increasingly important. The small particle size of the disclosed supported composites is consistent with these concerns.

[0048] The composites described herein can be used as fillers in epoxy molding compounds (EMCs). Epoxy molding materials are widely used in encapsulating semiconductor devices due to their excellent properties, such as high mechanical strength and high productivity. Generally, liquid epoxy polymers are injected onto the circuit and cured to a solid for protection. Here, the supported composites impart extremely low coefficient of thermal expansion (CTE), good dimensional stability, and flame retardancy to the packaging of semiconductor devices without significant increase in viscosity during the manufacturing process.

[0049] When referring to industrial composite prepreg applications, prepreg stands for "pre-impregnated" composite fibers. More specifically, prepreg is a composite material in which the reinforcing fibers are pre-impregnated with a thermoplastic or thermosetting resin matrix. This is a composite form that requires additional conversion or fabrication into a final fully cured part. Epoxy resin is the most common thermosetting polymer matrix material. The fibers are often in the form of a woven fabric, and the matrix is ​​used to glue them together or to other components during manufacturing. The thermosetting matrix is ​​only partially cured, making it easy to handle. This partially cured epoxy material may also be called a B-stage material. Composite prepregs are increasingly being used for high-performance applications in a variety of industrial sectors. Examples of the use of prepregs are aircraft interiors, aerospace parts, aircraft flooring, cargo liners, automotive parts and components, tools, bulletproof panels, electronic transmission applications, sporting goods, high-rise flooring, high-impact flooring, rotor blades wind turbines, and orthopedic technology in orthotics and prosthetics. The supported composites described herein, added as fillers, provide the necessary flame retardancy, very low coefficient of thermal expansion (CTE), and good dimensional stability. In applications requiring composite drilling, the supported zinc dimolybdate hydroxide / silica composites also improve drilling processability by reducing drilling defects, extending drill bit life, and reducing downtime.

[0050] The supported composites can also be used in thermal interface materials due to their high thermal conductivity and low viscosity due to the spherical shape of the particles. The supported composites (or the silica, or both the supported composites and the silica) can also be surface treated with silanes and / or other surfactants, such as epoxy silanes, phenylamino silanes, methacryl silanes, isocyanate silanes, etc. After surface treatment, the properties of the compound can be improved. Advantages include lower viscosity of the resin compound, better compatibility with polymer resins, and less agglomeration.

[0051] If desired, close-packing techniques, such as a combination of larger and smaller silica particles (e.g., a bimodal particle size distribution) rather than a single particle size distribution, can be applied to the supported composites to improve the viscosity of the compound at very high loading levels (up to 80 wt. % or more). EXAMPLES

[0052] The present invention is further illustrated by the following examples, which should not be construed as imposing limitations on the scope of the present invention in any way. After reading the description herein, various other embodiments, modifications, and equivalents thereof will be suggested to those skilled in the art without departing from the spirit of the present invention or the scope of the appended claims.

[0053] The d50 particle size, or median particle size, refers to the particle size at which 50% by weight of the sample has a smaller diameter and 50% of the sample has a larger diameter. Particle size measurements (including d10, d50, d90, and d100) were determined by laser diffraction according to ISO 13320 using a Beckman Coulter LS 13 320 single wavelength laser diffraction particle size analyzer.

[0054] BET surface areas were determined by Brunauer et al., J. Am. Chem. Soc., 60, 309 (1938) using a Micromeritics TriStar II surface area and porosity analyzer.

[0055] (Examples 1 to 11 and Comparative Example A) In Example 1, 161.8 g (1988 mmol) of zinc oxide (d50 of 0.31 μm, Zochem) and 1.25 L of deionized water were placed in a reaction vessel equipped with a stirrer and temperature controller and heated to 85° C. with stirring. Separately, 191.2 g (1328.4 mmol) of molybdenum trioxide (Langeloth Metallurgical Company) and 382.5 g of deionized water were added to a beaker to make a slurry at 85° C. Both were mixed well and the molybdenum trioxide slurry was pumped at 30 mL / min using a peristaltic pump into the reaction vessel containing the zinc oxide solution. The reaction mixture was then stirred at 85° C. for 1 hour, after which spherical fused silica (nominal d50 of 0.6 μm, d10 of 0.3 μm, d100 of 3 μm, and d100 of 6.2 μm) was added to the reaction vessel. 2 1412 g of 1,2-dichlorophenyl ether (BET surface area in g / g; Denka Co.; Figure 1 shows the sphericity of fused silica) was added and then stirred for another 6 hours. The resulting mixture was then poured into a glass pan and dried overnight in an oven at 120°C. The dried product was deagglomerated in a Henschel at 1800 rpm for 3 minutes and subsequently reduced to a specific particle size distribution by hammer mill grinding.

[0056] For Example 2A, 323.6 g (3976 mmol) of zinc oxide (d50 of 0.31 μm) and 2.5 L of deionized water were placed in a reaction vessel and heated to 85° C. with stirring. Separately, 382.4 g (2656.7 mmol) of molybdenum trioxide and 765 g of deionized water were added to a beaker to create a slurry at 85° C. Once both were well mixed, the molybdenum trioxide slurry was pumped at 30 mL / min using a peristaltic pump into the reaction vessel containing the zinc oxide solution. The reaction mixture was then stirred at 85° C. for 1 hour, after which spherical fused silica (nominal d50 of 0.4 μm, d10 of 0.2 μm, d100 of 0.8 μm, d100 of 11.3 μm) was added to the reaction vessel. 2 2824 g of 1,2-dichloroethane (BET surface area in mm / g; Denka Co., Ltd.) was added and stirred for an additional 6 hours. The resulting mixture was then poured into a glass pan and dried overnight in an oven at 120° C. The dried product was deagglomerated in a Henschel at 1800 rpm for 3 minutes and subsequently hammer milled to reduce the particle size distribution.

[0057] In Example 2B, 323.6 g (3976 mmol) of zinc oxide (d50 of 0.31 μm) and 2.5 L of deionized water were added to a reaction vessel and heated at 85° C. with stirring. Separately, 382.4 g (2656.7 mmol) of molybdenum trioxide and 765 g of deionized water were added to a beaker to make a slurry at 85° C. Once both were well mixed, the molybdenum trioxide slurry was pumped into the reaction vessel containing the zinc oxide solution at 30 mL / min using a peristaltic pump. The reaction mixture was then stirred at 85° C. for 1 hour, after which 1059 g of spherical fused silica (d50 of 0.4 μm) was added and stirred for an additional 6 hours. The resulting mixture was then poured into a glass pan and dried overnight in an oven at 120° C. The dried product was deagglomerated in a Henschel at 1800 rpm for 3 minutes, followed by hammer milling to reduce the particle size distribution to a specific size.

[0058] In Example 3, 50 g (614.3 mmol) of zinc oxide (d50 of 0.12 μm, Zochem Inc.) and 2.4 L of deionized water were placed in a reaction vessel and heated at 85° C. with stirring. Separately, 62.5 g (434.2 mmol) of molybdenum trioxide and 125 g of deionized water were added to a beaker to make a slurry at 85° C. Once both were well mixed, the molybdenum trioxide slurry was pumped into the reaction vessel containing the zinc oxide solution at 10 mL / min using a peristaltic pump. The reaction mixture was then stirred at 85° C. for 1 hour, after which 535 g of spherical fused silica (d50 of 4.12 μm, Imerys) was added and stirred for an additional 2 hours. The resulting mixture was then poured into a glass pan and dried overnight in an oven at 120° C. The dried product was deagglomerated in a Henschel at 1800 rpm for 3 minutes, followed by hammer milling to reduce the particle size distribution to a specific size.

[0059] In Example 4, 25 g (307.2 mmol) of zinc oxide (d50 of 0.12 μm) and 2.4 L of deionized water were placed in a reaction vessel and heated at 85° C. with stirring. Separately, 31.3 g (217.5 mmol) of molybdenum trioxide and 125 g of deionized water were added to a beaker to make a slurry at 85° C. Once both were well mixed, the molybdenum trioxide slurry was pumped into the reaction vessel containing the zinc oxide solution at 10 mL / min using a peristaltic pump. The reaction mixture was then stirred at 85° C. for 1 hour, after which 535 g of spherical fused silica (d50 of 4.12 μm, Imerys) was added and stirred for an additional 2 hours. The resulting mixture was then poured into a glass pan and dried overnight in an oven at 120° C. The dried product was deagglomerated in a Henschel at 1800 rpm for 3 minutes, followed by hammer milling to reduce the particle size distribution to a specific size.

[0060] In Example 4, 28 g (344 mmol) of zinc oxide (d50 of 0.12 μm) and 2.4 L of deionized water were placed in a reaction vessel and heated to 85° C. with stirring. Separately, 31.3 g (217.5 mmol) of molybdenum trioxide and 125 g of deionized water were added to a beaker to make a slurry at 85° C. Once both were well mixed, the molybdenum trioxide slurry was pumped into the reaction vessel containing the zinc oxide solution at 10 mL / min using a peristaltic pump. The reaction mixture was then stirred at 85° C. for 1 hour, after which 535 g of spherical fused silica (d50 of 0.6 μm, Imerys) was added and stirred for an additional 2 hours. The resulting mixture was then poured into a glass pan and dried overnight in an oven at 120° C. The dried product was deagglomerated in a Henschel at 1800 rpm for 3 minutes, followed by hammer milling to reduce the particle size distribution to a specific size.

[0061] In Example 6, 28 g (344 mmol) of zinc oxide (d50 of 0.12 μm) and 2.4 L of deionized water were placed in a reaction vessel and heated to 85° C. with stirring. Separately, 31.3 g (217.5 mmol) of molybdenum trioxide and 125 g of deionized water were added to a beaker to make a slurry at 85° C. Once both were well mixed, the molybdenum trioxide slurry was pumped into the reaction vessel containing the zinc oxide solution at 10 mL / min using a peristaltic pump. The reaction mixture was then stirred at 85° C. for 1 hour, after which 535 g of spherical fused silica (d50 of 0.6 μm, Imerys) was added and stirred for an additional 6 hours. The resulting mixture was then poured into a glass pan and dried overnight in an oven at 120° C. The dried product was deagglomerated in a Henschel at 1800 rpm for 3 minutes, followed by hammer milling to reduce the particle size distribution to a specific size.

[0062] In Example 7, 28 g (344 mmol) of zinc oxide (d50 of 0.12 μm) and 2.4 L of deionized water were placed in a reaction vessel and heated at 85° C. with stirring. Separately, 31.3 g (217.5 mmol) of molybdenum trioxide and 125 g of deionized water were added to a beaker to make a slurry at 85° C. Once both were well mixed, the molybdenum trioxide slurry was pumped into the reaction vessel containing the zinc oxide solution at 10 mL / min using a peristaltic pump. The reaction mixture was then stirred at 85° C. for 1 hour, after which 1070 g of spherical fused silica (d50 of 0.6 μm, Imerys) was added and stirred for an additional 6 hours. The resulting mixture was then poured into a glass pan and dried overnight in an oven at 120° C. The dried product was deagglomerated in a Henschel at 1800 rpm for 3 minutes, followed by hammer milling to reduce the particle size distribution to a specific size.

[0063] In Example 8, 50 g (614.3 mmol) of zinc oxide (d50 of 0.12 μm) and 2.4 L of deionized water were placed in a reaction vessel and heated at 50° C. with stirring. Separately, 62.5 g (434.2 mmol) of molybdenum trioxide and 125 g of deionized water were added to a beaker to make a slurry at 50° C. Once both were well mixed, the molybdenum trioxide slurry was pumped into the reaction vessel containing the zinc oxide solution at 10 mL / min using a peristaltic pump. The reaction mixture was then stirred at 50° C. for 1 hour, after which 535 g of spherical silica (d50 of 0.6 μm, Imerys) was added and stirred for an additional 6 hours. The resulting mixture was then poured into a glass pan and dried overnight in an oven at 120° C. The dried product was deagglomerated in a Henschel at 1800 rpm for 3 minutes, followed by hammer milling to reduce the particle size distribution to a specific size.

[0064] In Example 9, 50 g (614.3 mmol) of zinc oxide (d50 of 0.12 μm) and 2.4 L of deionized water were added to a reaction vessel and stirred at room temperature. Separately, 62.5 g (434.2 mmol) of molybdenum trioxide and 125 g of deionized water were added to a beaker to make a slurry at room temperature. Once both were well mixed, the molybdenum trioxide slurry was pumped into the reaction vessel containing the zinc oxide solution at 10 mL / min using a peristaltic pump. The reaction mixture was then stirred at room temperature for 1 hour, after which 1070 g of spherical silica (d50 of 0.6 μm) was added and stirred for an additional 6 hours. The resulting mixture was then poured into a glass pan and dried overnight in an oven at 120° C. The dried product was deagglomerated in a Henschel at 1800 rpm for 3 minutes, followed by hammer milling to reduce the particle size distribution to a specific size.

[0065] In Example 10, zinc dimolybdate hydroxide was produced in a similar manner to Example 1, except that the reaction mixture slurry (without added silica) was flash dried and then deagglomerated in a Micro ACM air classifier to form zinc dimolybdate hydroxide with a d50 of 3.3 μm. Then, 100 g of zinc dimolybdate hydroxide, 400 g of spherical fused silica (d50 of 0.6 μm), and 700 g of deionized water were placed in the grinding tank of an attritor mill without grinding media. The slurry mixture was then stirred at 600 rpm at about 22° C. for 6 hours. The resulting mixture was poured into a glass pan and dried overnight in an oven at 110° C. The dried product was deagglomerated in a Henschel at 1800 rpm for 3 minutes, followed by hammer milling to reduce the particle size distribution.

[0066] In Example 11, 20 g of zinc dimolybdate hydroxide (prepared in a manner similar to Example 10, d50 of 3.3 μm) and 80 g of spherical fused silica (d50 of 0.6 μm) were placed in a polypropylene bottle, and the bottle was placed in a modified Blue M oven and rotated overnight at approximately 22° C.

[0067] The spherical zinc dimolybdate hydroxide / silica composites produced in Examples 1-11 generally have a d10 particle size in the range of 0.3-0.5 μm, a d50 particle size in the range of 0.6-1.5 μm, a d100 particle size in the range of 4-5 μm, a particle size span in the range of 2.5-3, and a particle size span in the range of 5.5-9 μm. 2 / g range. The composites also had a zinc content of about 7 wt.% and a molybdenum content of about 7 wt.%, except for Example 2B, in which the zinc and molybdenum contents were independently about 14 wt.%.

[0068] Comparative Example A was prepared using the same silica as Example 1, but following the procedure described in U.S. Patent No. 6,190,787, the molybdenum trioxide and silica were mixed first, followed by the addition of zinc oxide. The composite obtained in Comparative Example A was compared to Example 1 (and representative of other examples) using XRD analysis to determine differences in crystal structure. Powder samples were loaded into a Panalytical X'pert MPD diffractometer using Cu radiation at 45 KV / 40 mA. Scans were performed in the range of 6°-80°, with a step size of 0.0131° and a count time of 250 seconds per step. After the diffraction patterns were obtained, phases were identified utilizing powder diffraction files or the Inorganic Crystal Structure Database published by the International Diffraction Data Center. The XRD data showed approximately 25 wt% of the amorphous phase due to silica, which was subtracted to yield the crystalline phase breakdown shown in Table I. Surprisingly, Example 1 was virtually all (approximately 99 wt%) zinc dimolybdate hydroxide (Zn3Mo2O8(OH)2), whereas Comparative Example A contained only about 60 wt% Zn3Mo2O8(OH)2, plus about 15 wt% hydrate (ZnMoO4·0.8H2O) and 25 wt% unknown crystalline phases.

[0069] Zinc and molybdenum-containing compounds can be difficult to adequately deposit on silica substrates. To illustrate the improvements disclosed herein, Figure 2 is a scanning electron micrograph (SEM) of the supported zinc dimolybdate hydroxide / silica composite of Example 1, while Figure 3 is an SEM of the composite of Comparative Example A. Advantageously, in contrast to Figure 3, where there are much more unsupported zinc molybdate particles that are not bound to the substrate silica support, Figure 2 shows that the zinc dimolybdate hydroxide is much more deposited on the silica.

[0070] (Examples 12 to 15) In Examples 13-15, the zinc dimolybdate hydroxide / silica complex was incorporated into plasticized polyvinyl chloride using a two-stage melt blend compounding process. In the first step, PVC, plasticizer, stabilizer, lubricant, antimony trioxide, ATH, and MgOH2 were mixed using a Henschel mixer at a temperature of 90°C to form a PVC premix having the composition shown in Table II. In the second step, 24.64 g of the zinc dimolybdate hydroxide / silica complex was added to 350.36 g of the PVC premix, which was then mixed for 5 minutes at 165°C and 45 rpm using a Brabender Intelli-Torque Plasti-Corder mixer with roller blades. Samples for analysis were prepared by pressing the material using a Givin PHI hydraulic press at a pressure of 78.3 bar and a temperature of 196°C. Example 12 utilized only the PVC premix, while Examples 13-15 utilized the zinc dimolybdate hydroxide / silica composites of Examples 9-11, respectively. Table III summarizes Examples 12-15 with their values ​​in phr.

[0071] A cone calorimeter (DEATAK CC-2) was used to test the flame retardancy of the samples according to the procedure described in ASTM E 1354. Specimens measuring 100 mm x 100 mm x 0.635 mm were exposed in a horizontal direction. The experiment was performed at 50 kW / m 2 An external heat flux of 0.01 was used. Measured parameters included time to sustained ignition, maximum heat release rate (PHRR), average 60 second heat release rate (RHR), total heat release (THR), average available heat of combustion, initial mass, final mass, sample mass loss, average mass loss rate (10%-90%), average SEA, maximum average heat release rate (MARHE), total smoke production, and average nominal total smoke production. Data reported were the average of three experiments.

[0072] Figure 4 shows the heat release rate (HRR) curves of the four flame retardant polymer compositions of Examples 12-15, and Table IV summarizes the flame retardant properties (from Figure 4). Advantageously and unexpectedly, the flame retardant compositions of Examples 13-15 (containing zinc dimolybdate hydroxide / silica composite) each had lower maximum heat release rate (PHRR; Example 13 had the lowest PHRR), total heat release rate (THR; Example 15 had the lowest THR), and maximum average heat release rate (MARHE; Example 14 had the lowest MARHE) values ​​than Example 12. Additionally, the total smoke yield and average nominal total smoke yield were significantly lower for Examples 13-15 than for Example 12.

[0073] (Examples 16 to 19) In Examples 16-19, silica or zinc dimolybdate hydroxide / silica composite was incorporated into the epoxy resin in the compositions (values ​​in phr) shown in Table V. Examples 17-19 utilized the zinc dimolybdate hydroxide / silica composites of Examples 1, 2B, and 2A, respectively. Example 16 used silica only. For each example, ten plaques measuring 100×100×7 mm were tested for wear and abrasion against a grinding / drill bit in removing a 2 mm thick layer of plaque.

[0074] FIG. 5 shows the drill bits before (top) and after (bottom) drilling of the epoxy plaques of Example 16 (reference 1) and Example 17 (reference 2), while FIG. 6 shows the drill bits before (top) and after (bottom) drilling of the epoxy plaques of Example 18 (reference 3) and Example 19 (reference 4). Unexpectedly and beneficially, the lower (post-milling) image shows that the epoxy plaques filled with 5 phr of spherical silica and 25 phr of supported zinc dimolybdate hydroxide / silica composite (Examples 17-19) perform much better (less wear, less abrasive) in terms of drillability than the epoxy plaque filled with 30 phr of spherical silica (Example 16). Arranged from most abrasive to least abrasive, they are Example 16 (reference 1), followed by Example 17 (reference 2) and Example 19 (reference 4), followed by Example 18 (reference 3). The abrasiveness correlated with the zinc / molybdenum content, with Example 16 containing none and being the most abrasive, and Example 18 containing the most and being the least abrasive. Examples 17 and 19 contained the same amount of zinc / molybdenum but had different silica particle sizes. Thus, particle size had little effect on abrasiveness compared to the amount of zinc / molybdenum in the epoxy formulation.

[0075] [Table 1]

[0076] [Table 2]

[0077] [Table 3]

[0078] [Table 4]

[0079] [Table 5]

[0080] The present invention has been described above with reference to numerous embodiments and specific examples. Numerous variations will occur to those skilled in the art in view of the above detailed description. All such obvious variations are included within the full intended scope of the appended claims. Other embodiments of the present invention include, but are not limited to, the following (embodiments may be described as "comprising" or alternatively may be "consisting essentially of" or "consisting of"):

[0081] Aspect 1. A method for making a supported zinc hydroxide dimolybdate / silica composite comprising: (i) reacting a zinc compound (e.g., zinc oxide, zinc chloride, zinc nitrate) with molybdenum trioxide (MoO3) in an aqueous system to form a reaction mixture; and (ii) contacting (or slurried) the reaction mixture with silica to form the supported zinc hydroxide dimolybdate / silica composite.

[0082] Aspect 2. The method of aspect 1, wherein step (i) and step (ii) can be independently carried out at a temperature within any suitable range, or within any range disclosed herein, e.g., 20°C to 95°C, 50°C to 95°C, 75°C to 90°C, or 80°C to 90°C.

[0083] Embodiment 3. The method of embodiment 1 or 2, wherein the zinc compound and molybdenum trioxide are reacted in any suitable range of Zn:Mo molar ratios, or any range of Zn:Mo disclosed herein, such as from 1:1 to 1:1 to 2:1, 1.2:1 to 1.8:1, 1.3:1 to 1.7:1, or 1.4:1 to 1.6:1, based on the total amount of each reactant.

[0084] Aspect 4. The method of any one of the preceding aspects, wherein step (i) and step (ii) are independently carried out at any suitable range of pressure, or any range of pressure disclosed herein, such as 5 psig to 100 psig, atmospheric pressure, or subatmospheric pressure.

[0085] Embodiment 5. A method of making a supported zinc dimolybdate hydroxide / silica composite, comprising contacting (or slurrying) zinc dimolybdate hydroxide with silica in an aqueous system to form a supported zinc dimolybdate hydroxide / silica composite.

[0086] Example 6. The method of Example 5, wherein the supported zinc dimolybdate hydroxide / silica composite is formed at a temperature in any suitable range or any range disclosed herein, e.g., 15°C to 95°C, 15°C to 50°C, or 20°C to 35°C.

[0087] Example 7. The method of example 5 or 6, wherein the supported zinc dimolybdate hydroxide / silica composite is formed at a pressure in any suitable range or any range disclosed herein, e.g., from 5 psig to 100 psig, atmospheric pressure, or subatmospheric pressure.

[0088] Embodiment 8. The method of any one of the preceding embodiments, further comprising removing the supported zinc dimolybdate hydroxide / silica composite from the water using any suitable technique, or any technique disclosed herein, such as filtration or centrifugation, as well as combinations thereof.

[0089] Embodiment 9. The method of any one of the preceding embodiments, further comprising drying the supported zinc dimolybdate hydroxide / silica composite under any suitable drying conditions, or any drying conditions disclosed herein, e.g., under a drying temperature ranging from 50° C. to 200° C., or from 100° C. to 150° C., and drying at atmospheric or subatmospheric pressure, e.g., less than 150 Torr, or less than 50 Torr.

[0090] Example 10. The method of any one of the preceding examples, further comprising deagglomerating the supported zinc hydroxide dimolybdate / silica composite, comminuting the supported zinc hydroxide dimolybdate / silica composite, or both.

[0091] Example 11. A supported zinc dimolybdate hydroxide / silica composite produced by the method of any one of examples 1 to 10.

[0092] Embodiment 12. A supported zinc dimolybdate hydroxide / silica composite comprising (a) silica and (b) zinc dimolybdate hydroxide in an amount ranging from 3 to 20 wt. %, based on the total weight of the supported zinc dimolybdate hydroxide / silica composite, wherein at least 80 wt. % of the zinc dimolybdate hydroxide is present in the crystalline form Zn3Mo2O8(OH)2.

[0093] Embodiment 13. The method or composite of any one of the preceding embodiments, wherein the silica is characterized by a median particle size (d50) of any suitable, or any range disclosed herein, such as 0.2-5 μm, 0.2-25 μm, 0.2-1 μm, or 0.25-0.8 μm.

[0094] Embodiment 14. The method or composite of any one of the preceding embodiments, wherein the silica is characterized by any suitable d100 particle size, or any range of d100 particle size disclosed herein, for example, a d100 particle size of 0.6-10 μm, 0.6-5 μm, 0.6-4 μm, 0.7-4 μm, or 0.7-3.5 μm.

[0095] Embodiment 15. The method or composite of any one of the preceding embodiments, wherein the silica is characterized by a d10 particle size of any suitable d10 particle size, or any range disclosed herein, e.g., 0.08-1 μm, 0.08-0.5 μm, 0.1-0.5 μm, or 0.1-0.4 μm.

[0096] Embodiment 16. The silica can have any suitable BET surface area, or any range disclosed herein, for example, 2 to 20 m 2 / g, 4~15m 2 / g, 4~12m 2 / g, 5-15m 2 / g, or 5-13m 2 23. The method or composite of any one of the preceding embodiments, wherein the composite is characterized by a BET surface area of ​​about 100 nm / g.

[0097] Example 17. The method or composite of any one of the preceding examples, wherein the silica is fused silica, or spherical silica, or spherical fused silica.

[0098] Embodiment 18. The supported zinc hydroxide dimolybdate / silica composite of any one of embodiments 11 to 17, wherein the supported zinc hydroxide dimolybdate / silica composite contains any suitable amount of zinc, or any range of amounts disclosed herein, such as 3-20 wt%, 3-18 wt%, 4-16 wt%, or 5-15 wt% zinc.

[0099] Embodiment 19. The supported zinc hydroxide dimolybdate / silica composite of any one of embodiments 11 to 18, wherein the supported zinc hydroxide dimolybdate / silica composite comprises any suitable amount of molybdenum, or any range of amounts disclosed herein, such as 3-20 wt%, 3-18 wt%, 4-16 wt%, or 5-15 wt% molybdenum.

[0100] Embodiment 20. The supported zinc dimolybdate hydroxide / silica composite of any one of embodiments 11 to 19, wherein the zinc dimolybdate hydroxide is present as Zn3Mo2O8(OH)2 in any suitable amount, or in any range of amounts disclosed herein, e.g., at least 80 wt%, at least 85 wt%, at least 90 wt%, or at least 95 wt%.

[0101] Embodiment 21. The supported zinc hydroxide dimolybdate / silica composite of any one of embodiments 11 to 20, wherein the supported zinc hydroxide dimolybdate / silica composite is characterized by a median particle size (d50) of any suitable, or any range disclosed herein, e.g., 0.3-6 μm, 0.3-2 μm, 0.4-1.8 μm, or 0.5-1.7 μm.

[0102] Embodiment 22. The supported zinc hydroxide dimolybdate / silica composite according to any one of embodiments 11-21, wherein the supported zinc hydroxide dimolybdate / silica composite is characterized by a d100 particle size of any suitable size, or any range disclosed herein, for example, 1-12 μm, 1-8 μm, 1.5-7 μm, 2-7 μm, or 2.5-6 μm.

[0103] Embodiment 23. The supported zinc hydroxide dimolybdate / silica composite of any one of embodiments 11 to 22, wherein the supported zinc hydroxide dimolybdate / silica composite is characterized by a d10 particle size of any suitable size, or any range disclosed herein, e.g., 0.1-1.5 μm, 0.1-0.8 μm, 0.1-0.7 μm, or 0.2-0.6 μm.

[0104] Embodiment 24. The supported zinc hydroxide dimolybdate / silica composite according to any one of embodiments 11 to 23, wherein the supported zinc hydroxide dimolybdate / silica composite is characterized by any suitable span ((d90-d10) / d50), or any range disclosed herein, such as a span of 1.5 to 5, 1.5 to 4.5, or 2 to 4.

[0105] Embodiment 25. The supported zinc dimolybdate hydroxide / silica composite can have any suitable BET surface area, or any range disclosed herein, e.g., 3-20 m 2 / g, 3-15m 2 / g, 3-12m 2 / g, 4~13mm 2 / g, or 4 to 10m 2 25. The supported zinc dimolybdate hydroxide / silica composite of any one of embodiments 11 to 24, characterized by a BET surface area of ​​100 / g.

[0106] Embodiment 26. The supported zinc hydroxide dimolybdate / silica composite of any one of embodiments 11 to 25, wherein the supported zinc hydroxide dimolybdate / silica composite is spherical.

[0107] Example 27. A polymer composition (or formulation) comprising: (a) a polymer; and (b) the supported zinc dimolybdate hydroxide / silica composite of any one of Examples 11 to 26.

[0108] Embodiment 28. The polymer composition of embodiment 27, wherein the amount of the supported zinc dimolybdate hydroxide / silica composite is any suitable amount or range of amounts disclosed herein, for example, 1 to 50 phr, 5 to 50 phr, 2 to 40 phr, 5 to 40 phr, 10 to 50 phr, 10 to 40 phr, 10 to 30 phr, or 15 to 40 phr.

[0109] Example 29. The polymer composition of example 27 or 28, wherein the polymer comprises any suitable polymer, or any polymer disclosed herein, such as a thermoplastic resin, a thermosetting resin, or a combination thereof.

[0110] Example 30. The polymer composition of example 27 or 28, wherein the polymer comprises polyvinylidene chloride (PVDC), polyvinyl chloride (PVC), chlorinated polyvinyl chloride (CPVC), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene chlorotrifluoroethylene (ECTFE), or any combination thereof.

[0111] Example 31. The polymer composition of example 27 or 28, wherein the polymer comprises rigid PVC.

[0112] Example 32. The polymer composition of example 27 or 28, wherein the polymer comprises soft PVC.

[0113] Example 33. The polymer composition of example 27 or 28, wherein the polymer comprises plasticized PVC or unplasticized PVC.

[0114] Example 34. The polymer composition of example 27 or 28, wherein the polymer comprises an epoxy resin.

[0115] Aspect 35. The polymer composition according to aspect 27 or 28, comprising bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, phenol novolac epoxy resin, cresol novolac epoxy resin, bisphenol A novolac epoxy resin, bisphenol F novolac epoxy resin, diphenylethylene epoxy resin, epoxy resin having a triazine skeleton, epoxy resin having a fluorene skeleton, triphenylmethane epoxy resin, biphenyl epoxy resin, xylylene epoxy resin, biphenyl aralkyl epoxy resin, naphthalene-based epoxy resin, dicyclopentadiene-based epoxy resin, alicyclic epoxy resin, or a combination thereof.

[0116] Aspect 36. The polymer composition according to any one of aspects 27 to 35, further comprising an additive, the additive comprising a stabilizer, a lubricant, an inorganic flame retardant (e.g., aluminum trihydrate or magnesium hydroxide), a filler, a colorant, a curing agent, a catalyst or accelerator, or a fiber (e.g., glass fiber, carbon fiber, paper fiber, nonwoven fiber), and any combination thereof.

[0117] Embodiment 37. The process, composite, or composition according to any one of embodiments 1 to 36, wherein the composite, the silica, or both the composite and the silica comprise a surface treatment (e.g., a silane surface treatment).

[0118] Example 38. An article of manufacture comprising the polymer composition defined in any one of examples 27 to 37.

[0119] Example 39. The article of example 38, wherein the article comprises a wire or cable.

[0120] Example 40. The article of example 38, wherein the article comprises a printed circuit board.

Claims

1. 1. A method for preparing a supported zinc dimolybdate hydroxide / silica composite, comprising the steps of: (i) Zinc compounds and molybdenum trioxide (MoO 3 ) in an aqueous system to form a reaction mixture; (ii) contacting the reaction mixture with silica to form the supported zinc dimolybdate hydroxide / silica composite; 1. A method for preparing a supported zinc dimolybdate hydroxide / silica composite comprising:

2. Step (i) and step (ii) are independently carried out at a temperature in the range of 20° C. to 95° C.; The zinc compound includes zinc oxide, The zinc oxide and the molybdenum trioxide are reacted in a molar ratio of Zn:Mo of 1:1 to 2:

1. The method of claim 1.

3. 1. A method for preparing a supported zinc dimolybdate hydroxide / silica composite, comprising the steps of: contacting zinc dimolybdate hydroxide with silica in an aqueous system to form the supported zinc dimolybdate hydroxide / silica composite; 1. A method for preparing a supported zinc dimolybdate hydroxide / silica composite comprising:

4. 4. The method of claim 3, wherein the supported zinc dimolybdate hydroxide / silica composite is formed at a temperature in the range of 15°C to 95°C.

5. 10. The method of claim 1 further comprising the step of removing the supported zinc dimolybdate hydroxide / silica composite from the water.

6. drying the supported zinc dimolybdate hydroxide / silica composite; deagglomerating the supported zinc dimolybdate hydroxide / silica composite; grinding the supported zinc dimolybdate hydroxide / silica composite; or The method of claim 1 further comprising any combination thereof.

7. 2. The supported zinc dimolybdate hydroxide / silica composite produced by the method of claim 1.

8. (a) silica; (b) zinc dimolybdate hydroxide containing zinc in an amount ranging from 3 to 20 wt %, based on the total weight of the supported zinc dimolybdate hydroxide / silica composite; Including, At least 80 wt. % of the zinc dimolybdate hydroxide is in the crystalline form Zn 3 M.O. 2 O 8 (OH) 2 A supported zinc dimolybdate hydroxide / silica composite present as:

9. The silica is A d50 particle size of 0.2 to 5 μm; A d100 particle size of 0.6 to 10 μm; A d10 particle size of 0.08 to 1 μm; A BET surface area of ​​2 to 20 m2 / g; 2. The method or complex of claim 1, having the following structure:

10. The silica is fused silica or The silica is spherical silica, or or both, 2. The process or complex of claim 1.

11. the supported zinc dimolybdate hydroxide / silica composite contains 4-16 wt % zinc; the supported zinc dimolybdate hydroxide / silica composite contains 3-20 wt % molybdenum; At least 90 wt % of the zinc dimolybdate hydroxide is Zn 3 M.O. 2 O 8 exists as (OH) 2. The process or complex of claim 1.

12. The supported zinc dimolybdate hydroxide / silica composite is A d50 particle size of 0.3 to 6 μm; A d100 particle size of 1 to 12 μm; A d10 particle size of 0.1 to 1.5 μm; Span of 1.5 to 5 ((d90-d10) / d50) and A BET surface area of ​​3 to 20 m2 / g; 2. The process or complex of claim 1, having the formula:

13. 2. The process or composite of claim 1, wherein the supported zinc dimolybdate hydroxide / silica composite is spherical.

14. (a) a polymer; (b) the supported zinc dimolybdate hydroxide / silica composite of claim 7; and 1. A polymer composition comprising:

15. The polymer composition of claim 14 , wherein the polymer comprises a thermoplastic polymer.

16. The polymer composition of claim 14 , wherein the polymer comprises a thermoset polymer.

17. 15. The polymer composition of claim 14, wherein the polymer comprises rigid PVC or flexible PVC.

18. The polymer composition of claim 14 , wherein the polymer comprises an epoxy resin.

19. 15. The polymer composition of claim 14, wherein the amount of the supported zinc dimolybdate hydroxide / silica composite ranges from 1 to 50 phr.

20. 15. The polymer composition of claim 14, wherein the polymer composition further comprises an additive, the additive comprising a stabilizer, a lubricant, an inorganic flame retardant, a filler, a colorant, a curing agent, a catalyst or accelerator, a fiber, or any combination thereof.

21. 15. An article of manufacture comprising the polymer composition of claim 14.

22. 22. The article of claim 21, wherein the article comprises a wire or cable.

23. The article of claim 21 , wherein the article comprises a printed circuit board.